FORMATION AND DEVELOPMENT OF THE ASEAN POLITICAL-SECURITY COMMUNITY - ВАРТОВНИК, Іван (Київський національний університет імені Т. Шевченка, 2025)
Background. The Association of Southeast Asian Nations (ASEAN) is a regional association of 10 countries, namely: Indonesia, Malaysia, Singapore, the Philippines, Thailand, Brunei, Vietnam, Laos, Myanmar and Cambodia. This Association has managed not only to ensure peace and stability in Southeast Asia (SEA), but also to play a leading role in establishing and promoting a security architecture in the Asia-Pacific region (APAC) through the promotion of cooperative security. In this regard, there is a need to analyze the foundations of ASEAN's functioning and its security policy, which is implemented through the ASEAN Political-Security Community, the key structure where all ASEAN political and security activities converge. However, the question arises as to the principles of this Political-Security Community, its creation, development and prospects for further functioning in the security environment of the Asia-Pacific region. Methods. The following methods were used in the research: problem-chronological and comparative analysis. Results. The normative legal documents of the Association of Southeast Asian Nations (ASEAN), such as the Bali Declarations, the ASEAN Charter and the Political-Security Community Blueprints, have created the foundation for the functioning and development of the ASEAN Political-Security Community (APSC). These documents provide a regulatory framework for cooperative security and define its principles in ASEAN's activities. The ASEAN Political-Security Community has demonstrated the ability to adapt to changes in the regional and global security environment. This includes expanding its role from the regional to the global level, especially in the area of cross-border challenges. Conclusions. The ASEAN Political-Security Community continues to develop in accordance with the ASEAN Political-Security Community Blueprint for 2016-2025. This process envisages long-term and strengthened ASEAN political and security cooperation, which will have an impact on the security of the wider Asia-Pacific region in the medium and long term perspectives.

Вступ. Асоціація держав Південно-Східної Азії (АСЕАН) – регіональне об’єднання 10 країн, а саме: Індонезії, Малайзії, Сінгапуру, Філіппін, Таїланду, Брунею, В’єтнаму, Лаосу, М’янми та Камбоджі. Дана Асоціація спромоглася не тільки забезпечити мир та стабільність у Південно-Східній Азії (ПСА), а й відіграти провідну роль у встановленні та поступі безпекової архітектури в Азійсько-Тихоокеанському регіоні (АТР) через просування кооперативної безпеки. У зв’язку з цим виникає потреба проаналізувати основи функціонування АСЕАН та її безпекової політики, що втілюється через Політико-Безпекову Спільноту АСЕАН – ключову структуру, де сходиться вся політична та безпекова діяльність АСЕАН. Однак виникає питання щодо засад діяльності даної Політико-Безпекової Спільноти, її створення, розвитку та перспектив подальшого функціонування у безпековому середовищі Азійсько-Тихоокеанського регіону. Методи. Під час дослідження були використані такі методи: проблемно-хронологічний та порівняльний аналіз. Результати. Нормативно-правові документи Асоціації держав Південно-Східної Азії (АСЕАН), такі як Балійські Декларації, Хартія АСЕАН та Концепції розбудови Політико-Безпекової Спільноти АСЕАН створили фундамент для функціонування та розвитку Політико-Безпекової Спільноти АСЕАН (ПБСА). Ці документи забезпечують нормативну основу для кооперативної безпеки та визначають її принципи у діяльності АСЕАН. Політико-Безпекова Спільнота АСЕАН продемонструвала здатність адаптуватися до змін у регіональній та глобальній безпековій обстановці. Це включає розширення її ролі від регіонального до глобального рівня, особливо у сфері транскордонних викликів. Висновки. Політико-Безпекова Спільнота АСЕАН продовжує свій розвиток відповідно до Концепції розбудови Політико-Безпекової Спільноти АСЕАН на 2016-2025 роки. Цей процес передбачає довготривалість та посилення політико-безпекового співробітництва Асоціації країн Південно-Східної Азії, що матиме вплив на безпеку ширшого Азійсько-Тихоокеанського регіону в середньо- та довгостроковій перспективі.
СТАНОВЛЕННЯ ТА РОЗВИОК ПОЛІТИКО-БЕЗПЕКОВОЇ СПІЛЬНОТИ АСЕАН
Keywords: ASEAN; ASEAN Political-Security Community; cooperative security; Asia-Pacific; АСЕАН; Політико-Безпекова Спільнота АСЕАН; кооперативна безпека; Азійсько-Тихоокеанський регіон; кооперативна безпека; регіональні міждержавні організації; безпека Азійсько-Тихоокеанського регіону